Coastal zones : solutions for the 21st century - Baztan, Juan (Amsterdam : Elsevier, 2015)
Chapter 1 - Paradigm Shifts, Coastal Zones, and Adaptation to Fast-Paced Change: Moving Toward Transdisciplinary Community-Centered Approaches -- Chapter 2 - Transfer of Knowledge and Mutual Learning on the Canadian Atlantic Coast -- Chapter 3 - Coastal Population and Land Use Changes in Europe: Challenges for a Sustainable Future -- Chapter 4 - Human Frontiers: An Act of Smuggling Across Social Borders -- Chapter 5 - Sustainable Mariculture at High Latitudes -- Chapter 6 - Coastal Governance Solutions Development in Latvia: Collaboration Communication and Indicator Systems -- Chapter 7 - Geoengineering Coastlines? From Accidental to Intentional -- Chapter 8 - Remote Sensing Solutions to Monitor Biotic and Abiotic Dynamics in Coastal Ecosystems -- Chapter 9 - Managing Adaptation to Changing Climate in Coastal Zones -- Chapter 10 - Sustainability of Artificial Coasts: The Barcelona Coast Case -- Chapter 11 - Protected Shores Contaminated with Plastic: From Knowledge to Action -- Chapter 12 - Challenges to Sustainable Development along Peruvian Coastal Zones -- Chapter 13 - Solutions for Sustainable Coastal Lagoon Management: From Conflict to the Implementation of a Consensual Decision Tree for Artificial Opening -- Chapter 14 - Challenges to Evaluating Coastal Management in the Twenty-First Century: Lessons from the Lofoten Archipelago -- Chapter 15 - Motivation for the Viability of the Lobster Fishery: Case Study of the Acadian Coast of New Brunswick -- Chapter 16 - Lobster Fisheries in Atlantic Canada in the Face of Climate and Environmental Changes: Can We Talk About Sustainability of These Coastal Communities? -- Chapter 17 - Universities as Solutions to Twenty-First Century Coastal Challenges: Lessons from Cheikh Anta Diop Dakar University -- Chapter 18 - Engaging Local Communities for Climate Change Adaptation: A Case Study in Quebec, Canada -- Chapter 19 - Conclusion.
COASTAL ZONES AS COMPLEX SYSTEMS -- THE EVOLUTION OF SCIENCE AT CHEIKH ANTA DIOP UNIVERSITY -- REFERENCES -- Making the Link -- Chapter 18 -- Engaging Local Communities for Climate Change Adaptation: A Case Study in Quebec, Canada -- INTRODUCTION -- COMMUNITY RESILIENCE CAPACITY BUILDING -- PARTICIPATORY ACTION RESEARCH -- METHOD OF EVALUATION BY GROUP FACILITATION -- INITIATING COMMUNITY PLANNING FOR RESILIENCE IN BONAVENTURE -- DISCUSSION -- CONCLUSIONS -- ACKNOWLEDGMENTS -- REFERENCES -- Chapter 19 -- Conclusion -- APPENDIX -- INPUT FOR THE COMPILATION DOCUMENT FROM THE "COASTAL ZONES: 21ST CENTURY CHALLENGES" WORKING GROUP -- INTRODUCTION -- CONCLUSION -- REMINDER -- Index.
Online resource; title from PDF title page (Ebsco, viewed June 3, 2015).
Includes bibliographical references and index.
Keywords: Integrated coastal zone management; Climatic changes; Sustainable development; POLITICAL SCIENCE -- Public Policy -- Regional Planning; Climatic changes; Integrated coastal zone management; Sustainable development; 2; Regionalentwicklung; Nachhaltigkeit; Electronic books; Electronic book